2023
DOI: 10.1186/s12989-023-00517-x
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons in urban particle matter exacerbate movement disorder after ischemic stroke via potentiation of neuroinflammation

Abstract: Background A recent epidemiological study showed that air pollution is closely involved in the prognosis of ischemic stroke. We and others have reported that microglial activation in ischemic stroke plays an important role in neuronal damage. In this study, we investigated the effects of urban aerosol exposure on neuroinflammation and the prognosis of ischemic stroke using a mouse photothrombotic model. Results When mice were intranasally exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The brain was isolated and cryoprotected in 30% sucrose, and then was frozen in powdered dry ice, and 50‐μm‐thick floating sections including hippocampus area were prepared using a Cryostat (CM3050 S; Leica Biosystems). The brain sections were stained with Iba1, CD68, and DAPI to calculate the number of microglia, the microglial soma area and CD68 expression in microglia, according to our previous reports 19,20 . The antibodies used in this study were listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The brain was isolated and cryoprotected in 30% sucrose, and then was frozen in powdered dry ice, and 50‐μm‐thick floating sections including hippocampus area were prepared using a Cryostat (CM3050 S; Leica Biosystems). The brain sections were stained with Iba1, CD68, and DAPI to calculate the number of microglia, the microglial soma area and CD68 expression in microglia, according to our previous reports 19,20 . The antibodies used in this study were listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The brain sections were stained with Iba1, CD68, and DAPI to calculate the number of microglia, the microglial soma area and CD68 expression in microglia, according to our previous reports. 19,20 The antibodies used in this study were listed in Table 1. Stained sections were observed laser-scanning microscopy (LSM700; Carl Zeiss, Oberkochen, Germany).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Metal contents in PM2.5 were measured by IDEA Consultants, Inc. (Tokyo, Japan) using inductively coupled plasma-mass spectrometry. PAHs in PM2.5 were determined using GC-MS (7890A/5957C, Agilent, Palo Alto, CA, USA) according to our previous report (Tanaka et al, 2023). Endotoxin levels in the PM2.5 were measured using an Endospecy ES-50M set (Seikagaku Co., Tokyo, Japan) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to BaP has a direct effect on brain function since BaP and its metabolites can accumulate in lipid-rich tissues such as the brain [68] and have been shown to impair the blood-brain barrier function [69]. Tanaka et al demonstrated that exposure to PAHs altered stroke outcomes in mice after intranasal exposure, which induced edema in the brain and impaired locomotor functions in rats [70]. These findings suggest that despite the liver's primary role in detoxifying xenobiotics [71], there exists a tissue-specific vascular response, potentially highlighting the link between certain PAHs and stroke pathophysiology.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…Further evidence supports the idea that environmental toxins can alter the lung-brain axis and may influence the likelihood of stroke onset and post-stroke outcomes. Tanaka et al demonstrated that intranasal exposure to urban aerosols in mice can affect post-stroke recovery by augmenting neuroinflammation, activating brain resident microglial cells, and impairing motor function post-stroke [70].…”
Section: Lung-brain Axis and Environmental Toxinsmentioning
confidence: 99%